Serum Magnesium Level in Diabetic and Hypertensive Patients with Ischemic Stroke - Islam, Md Zahidul; Sultana, Syeda Aleya; Mostafi, Mamun; Kawnayn, Ghulam; Akter, Tania (Bangladesh Armed Forces Medical Journal, 2025)
Background: Stroke is a prevalent medical emergency and a leading cause of mortality, with increasing incidence in many lower- and middle-income countries due to unhealthy lifestyle practices. Among the two main types of stroke, ischemic stroke accounts for approximately 85% of cases. Study Aim: This study aimed to determine serum magnesium levels in patients with ischemic stroke who also have a history of diabetes and hypertension. Methods: This observational study was conducted in the Medicine Department at Combined Military Hospital from July to December 2015, involving patients with acute ischemic stroke who also had diabetes and hypertension. A total of 51 patients meeting the inclusion criteria were selected using purposive probability sampling. Results: Of the 51 patients assessed, 33 were male and 18 were female, with average ages of 62.89±10.45 years for males and 65.75±9.78 years for females. Hypertension was controlled in 18 patients and uncontrolled in 33; similarly, diabetes was controlled in 12 and uncontrolled in 39 patients. Control of diabetes was defined as HbA1c < 7% over the past three months, while control of blood pressure was defined as BP < 140/90 mm Hg over the same period. The average serum magnesium level across all subjects was 0.69±0.11 mmol/l. Hypomagnesemia was observed in 66.7% (34) of patients, with an average serum magnesium level of 0.63±0.049 mmol/l in these individuals. Mean serum magnesium levels in patients with controlled and uncontrolled blood pressure were 0.80±0.03 mmol/l and 0.63±0.01 mmol/l, respectively. Among those with controlled and uncontrolled diabetes, mean serum magnesium levels were 0.73±0.13 mmol/l and 0.67±0.10 mmol/l, respectively. Conclusion: Serum magnesium levels are low in acute ischemic stroke, hypertension and diabetes are associated. Bangladesh Armed Forces Med J Vol 57 No (2) December 2024, pp 21-28